463 Broiler chickens express differential alkaline phosphatase activity and enzyme affinity in hydrolyzing ATP along the small intestinal longitudinal axis. (1st August 2017) - Zhou, K.; Burello, N.; Wang, W.; Archbold, T.; Leung, H.; Kiarie, E.; Fan, M. Z.
Abstract: Broiler chicken growth rates are rapidly accelerating in the industry, requiring an average of 6 to 7 weeks to achieve market body weight. A possible determinant is intestinal alkaline phosphatase (IAP), a key enzyme which dephosphorylates pathogen-associated-molecular patterns (PAMPs) such as endotoxin lipopolysaccharides (LPS) and ATP, thereby preventing gut dysbosis and disorders. However, IAP's roles in maintaining gut health have yet to be elucidated in the broiler chicken. Thus, the objective of this study was to determine IAP activity kinetics for hydrolyzing ATP at pH 7.4 and 41°C in the duodenal, jejunal, and ileal segments of young broilers. Ten 28-d old broiler (Ross 708) chickens, maintained on a standard grower corn soybean meal diet, were euthanized for collecting duodenal, jejunal, and ileal tissue samples. Each ATP kinetic experiment was conducted with 20 gradient concentrations of ATP in 4 replicates, ranging 0 – 5 mM in incubation media. All enzymatic incubations were conducted with about 3 µg protein of the homogenized small intestinal segmental tissues. The kinetics (parameter estimates ± SE, P < 0.05, R 2 = 0.82 – 0.93; n = 80) of the broiler small intestinal segmental IAP activities of hydrolyzing ATP were obtained, including Vmax values (µg/mg protein·min) of 7.59 ± 0.09, 8.60 ± 0.16, and 7.77 ± 0.19; and Km values (mM) of 0.045 ± 0.004, 0.132 ± 0.015, and 0.105 ± 0.015 in the duodenum, jejunum, and ileum, respectively. Pooled t-tests showed that the Vmax was higher ( P < 0.05) in the jejunum than in the duodenum and the ileum, while the Vmax value was higher ( P < 0.05) in the ileum than in the duodenum. Furthermore, the Km value was lower ( P < 0.05) in the duodenum than in the jejunum by 2-fold and the ileum by 1.3-fold, respectively, while the Km value was lower ( P < 0.05) in the ileum than in the jejunum by 26%. Our results suggest that young broiler chickens express differential alkaline phosphatase activity and enzyme affinity in hydrolyzing ATP along the small intestinal longitudinal axis.